Field and minerological constraints of the Dir metavolcanic sequence, Kohistan Arc terrane, northern Pakistan - Shah, Mohammad Tahir; Hamidullah, Syed (Journal of Himalayan Earth Sciences, 1994)
The Dir metavolcanic sequence, a part of the Dir group, constitutes a NE-SW trending belt within the northwestern portion of the Kohistan island arc in the western Himalayas of northern Pakistan. This sequence is dominantly composed of basaltic-andesite and andesite with subordinate basalt, dacite, rhyolite, and pyroclastic breccia. These rocks are foliated and sheared along local faults and also have small intrusions at places. Porphyritic textures are dominant, with less common aphyric and seriate textures. Plagioclase (An1042) is ubiquitous in all the members of the sequence and occurs as phenocrysts and in groundmass. K-feldspar and quartz predominate both as phenocrysts of the dacites and rhyolites. Chlorite, epidote, and actinolite are the most common metamorphic phases; hornblende, muscovite, biotite, kaolinite, sericite, carbonate, and opaques occur rarely. Phase assemblages and chemistry suggest predominant greenschist facies metamorphism with epidote-amphibolite facies conditions attained locally.